Epidural bupivacaine combined with dexmedetomidine or clonidine in infraumbilical surgeries: a comparative evaluation - Agarwal, Shilpi; Singh, Rakesh Bahadur; Singh, Dheer; Kumar, Manoj; Mishra, Prashant Kumar; Bhardwaj, Bharat Bhushan (International Journal of Research in Medical Sciences, 2017)
Background: Alpha-2 agonist are being extensively evaluated as an alternative to neuraxial opoids, as an adjuvants in regional anaesthesia The faster onset of action of local anaesthetics, rapid establishment of both sensory and motor blockade, prolonged duration of analgesia into postoperative period, dose sparing action of local anaesthetics and stable cardiovascular parameters make these agents a very effective adjuvant in regional anaesthesia. Methods: Our study had 45 patients, all patients belonged to ASA Grade-I or II, between 20 and 55 years of age with an average height of 150 and 170 cm and have ideal body weight requiring neuraxial blockade for lower abdominal surgeries. All the patients were randomly allocated into two groups Group-I: Epidural bupivacaine 0.5% (16 ml) + clonidine 75 µgm (1 ml) Group-II: Epidural bupivacaine 0.5 % (16 ml) + Dexmedetomidine 50 µgm (1 ml) Patients were monitored for sensory and motor blockade, hemodynamic parameters, rescue analgesia, sedation and adverse effects in perioperative period. Results: The time of onset of sensory block at T10 and time to reach maximum sensory block (T6) in group-I was significantly longer as compared to group-II. The complete motor blockade (grade-3) was achieved much later and time taken for recovery to grade-0 was significantly shorter in group-I. The time for rescue analgesia in group-I was significantly shorter as compared to group-II. Hypotension was the most common side effect in both the groups. Dry mouth is a known side effect of alpha-2 agonists. Epidural dexmedetomidine produced profound sedation. Conclusions: We conclude from this study that dexmedetomidine is a better adjuvant than clonidine for providing early onset of sensory analgesia, superior sedative properties and prolonged post-operative analgesia.